Back cover: Subtle Alterations in DNA Methylation Patterns in Normal Cells in Response to Dietary Stilbenoids. Issue 14 (23rd July 2018) - Beetch, Megan; Lubecka, Katarzyna; Kristofzski, Heather; Suderman, Matthew; Stefanska, Barbara
Abstract : Mol. Nutr. Food Res. 2018, 62, 1800193 DOI:10.1002/mnfr.201800193 In article number1800193, Barbara Stefanska and co‐workers detect subtle alterations in DNA methylation in normal cells and blood of healthy rats exposed to dietary polyphenols of the stilbenoid class. Differentially methylated genes are involved in functions indicating a role for alterations in DNA methylation in stabilizing control mechanisms to maintain a healthy phenotype. Such molecular markers can be used as an excellent tool to reliably measure long‐term polyphenol exposure and establish associations between polyphenol intake and risk of chronic diseases.